PENGARUH TINGKAT KECUKUPAN MODAL TERHADAP PROFITABILITAS DENGAN RISIKO KREDIT SEBAGAI VARIABEL PEMODERASI - Minar Savitri, Dhian Andanarini (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2016)
This study analyzed the influence of bank capital adequacy level toprofitability by using credit risk as moderating variable. The data used inthis study is conventional banking listed on the IDX period 2011-2014.The results of this study indicate that the capital adequacy does notaffect the profitability, credit risk negatively affect profitability and creditrisk can not moderate the influence of capital adequacy rate on bankprofitability in Indonesia